Key Factors in Clinical Competency Committee Members' Decisions Regarding Residents' Readiness to Serve as Supervisors: A National Study. (February 2019) - Schumacher, Daniel J.; Martini, Abigail; Bartlett, Kathleen W.; King, Beth; Calaman, Sharon; Garfunkel, Lynn C.; Elliott, Sean P.; Frohna, John G.; Schwartz, Alan; Michelson, Catherine D.
Abstract : Purpose: Entrustment has become a popular assessment framework in recent years. Most research in this area has focused on how frontline assessors determine when a learner can be entrusted. However, less work has focused on how these entrustment decisions are made. The authors sought to understand the key factors that pediatric residency program clinical competency committee (CCC) members consider when recommending residents to a supervisory role. Method: CCC members at 14 pediatric residency programs recommended residents to one of five progressive supervisory roles (from not serving as a supervisory resident to serving as a supervisory resident in all settings). They then responded to a free-text prompt, describing the key factors that led them to that decision. The authors analyzed these responses, by role recommendation, using a thematic analysis. Results: Of the 155 CCC members at the participating programs, 84 completed 769 supervisory role recommendations during the 2015–2016 academic year. Four themes emerged from the thematic analysis: (1) Determining supervisory ability follows from demonstrated trustworthiness; (2) demonstrated performance matters, but so does experience; (3) ability to lead a team is considered; and (4) contextual considerations external to the resident are at play. Conclusions: CCC members considered resident and environmental factors in their summative entrustment decision making. The interplay between these factors should be considered as CCC processes are optimized and studied further. Abstract : Supplemental Digital Content is available in the text.